Decision Making Among Persons Living With Heart Failure. Issue 5 (September 2016) - Xu, Jiayun; Abshire, Martha; Han, Hae-Ra
Abstract : Background: Persons with heart failure (HF) are required to make decisions on a daily basis related to their declining health and make urgent decisions during acute illness exacerbations. However, little is known about the types of decisions patients make. Objective: The aims of this study were to critically evaluate the current quantitative literature related to decision making among persons with HF and identify research gaps in HF decision-making research. Methods: A systematic search of literature about decisions persons with HF make was conducted using PubMed, CINAHL, and PsychINFO databases. The following inclusion criteria were used: sample composed of at least 50% HF participants, concrete decisions were made, and a quantitative study design was used. Two authors performed title, abstract, and full-text reviews independently to identify eligible articles. Results: Twelve quantitative articles were included. Study samples were predominately older, white, male, and married. Two-thirds of the articles focused on decisions related to the end-of-life topics (ie, resuscitation decisions, advanced care planning). The other one-third focused on decisions about care seeking, participant's involvement in treatment decisions during their last clinic visit, and self-care behaviors. Conclusions: Within the HF literature, the term decision is often ill-defined or not defined. Limitations in methodological rigor limit definitive conclusions about HF decision making. Future studies should consider strengthening study rigor and examining other decision topics such as inclusion of family in making decisions as HF progresses. Research rigorously examining HF decision making is needed to develop interventions to support persons with HF.